Saussurea qilianshanensis (Asteraceae, Cardueae), a new species of Saussurea from Gansu, China - Du, Si-Yi; Li, Tian; Xu, Lian-Sheng; An, Guo-Qing; Chen, You-Sheng (Phytotaxa, 2025)
Saussurea qilianshanensis, a new species from Gansu, China, is described and illustrated herein. It differs from S. yabulaiensis by its stems 15–40 cm tall (vs. 12–20 cm), leaf lobes linear (vs. linear or narrowly lanceolate), leaf surfaces sparsely arachnoid and gland-dotted (vs. sparsely gland-dotted or glabrous), phyllaries purple and arachnoid (vs. green and glandular hairy). Molecular systematic analyses based on Hyb-Seq data confirm that S. qilianshanensis is a new species belonging to S. subg. Theodorea.